PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP MOTIVASI BELAJAR DI SMP NEGERI 1 MAKASSAR - Salama, Muhammad Arisullah; Syahid, Akhmad; Surani; Bunyamin, Andi; Syahrul, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Posing learning model on the learning motivation—both intrinsic and extrinsic—of eighth-grade students in the Islamic Religious Education subject at SMP Negeri 1 Makassar. The study employs a quantitative approach using an *ex post facto* method. The population consists of all 327 eighth-grade students at SMP Negeri 1 Makassar. A sample of 62 students was selected using Slovin's formula with a 10% margin of error. Data collection involved questionnaires and documentation, while the research instrument utilized a Likert scale. Data analysis was conducted using SPSS software, encompassing descriptive analysis, validity and reliability testing, assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results indicate that the Problem Posing learning model has a positive and significant effect on students' intrinsic learning motivation. This is evidenced by a calculated t-value of 6.000 (exceeding the t-table value of 2.001) and a significance value of 0.001 (below 0.05). The Problem Posing model also has a positive and significant effect on extrinsic learning motivation, with a calculated t-value of 4.701 (exceeding the t-table value of 2.001) and a significance value of 0.001 (below 0.05). The R-Square values ​​indicate that the Problem Posing model contributes 67.5% to intrinsic motivation and 50.9% to extrinsic motivation. Thus, the Problem Posing learning model serves as an effective alternative for enhancing student learning motivation in Islamic Religious Education.